2019
DOI: 10.1590/s0100-83582019370100070
|View full text |Cite
|
Sign up to set email alerts
|

Period of Weed Interference in Guarana Crop

Abstract: Guarana is a plant native to the Amazon region that produces the fruit known as guarana. Guarana production is carried out by small farmers and is a source of income for thousands of people in rural and urban areas. The interference caused by the competition between weeds and guarana is an important limiting factor of its production. Despite its economic and social importance, there are few studies on the management of weeds in this species. Thus, this research aimed to study the effects of weed interference o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In recent surveys on critical period of weed interference in orange tree and guarana crops conducted in Amazonas State, there was a loss of productivity compared to control of 34% for orange (Gonçalves et al, 2018) and 65% for guarana (Soares et al, 2019).…”
Section: Productivity and Periods Of Interference Of Weed Plantsmentioning
confidence: 99%
“…In recent surveys on critical period of weed interference in orange tree and guarana crops conducted in Amazonas State, there was a loss of productivity compared to control of 34% for orange (Gonçalves et al, 2018) and 65% for guarana (Soares et al, 2019).…”
Section: Productivity and Periods Of Interference Of Weed Plantsmentioning
confidence: 99%
“…Weed interference reduces guarana production by up to 65%. Therefore, weed management is necessary to enable production [ 4 ]. The use of herbicides has advantages over mechanical control since it is more efficient in controlling aggressive weed species and in high air relative humidity and abundant rainfall conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Among phytosanitary factors, weed control has great relevance in the production of guarana. The research of Soares, Albertino, Souza, Santos, and Silva (2019) found that in areas without weed control, production may be reduced by up to 50%. Although some studies have found evidence that the use of herbicides is efficient and cheap for weed control in guaranazeiro crops, there are no registered products in Brazil (Fontes & Nascimento Filho, 2007).…”
Section: Introductionmentioning
confidence: 99%